(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Landslides are the most across the board natural disaster in Sikkim which builds its spatial degree for quite a while. Landslide is a common natural phenomenon seen in mountainous territory of Sikkim. It is the most unavoidable of natural dangers that undermine the economic and social advancement of Sikkim. Natural elements like rainstorms, quake can trigger landslides. It brings an extraordinary death toll and substantial harm to land and property. The fundamental goal of the present examination is to distinguish the reasons for landslides, their effect and to propose vital measures to alleviate the risk in the Sikkim. The discoveries of the present examination uncovers that it is neither conceivable to stop the landslides nor to totally wipe out their harms however it is conceivable to limit the seriousness of the effect and the harm potential through a few basic measures and settlement strategy with solid open mindfulness.